Increasing the Results and Interest in Learning Civics through a Problem-Based learning Model for 1st Grade Students - Wardani, Niken Tri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to improve Civics learning outcomes through the Problem Based Learning method for students of SD Negeri Ngemplak class, Karangnongko, Klaten Semester I of the 2021/2022 academic year. The subjects in the study were the process and learning outcomes of Civics in grade 1 students of SD Negeri Ngemplak, Karanongko, Klaten. semester I of the 2021/2022 academic year consisting of 19 students, namely 10 boys and 9 girls. The research procedure used is a classroom action research type procedure which is carried out in 2 cycles, each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. Data analysis, qualitative data from observations of the learning process were analyzed using qualitative descriptive analysis by comparing cycle I with cycle II, while data in the form of numbers (quantitative data) from student learning outcomes were analyzed using comparative descriptive namely comparing initial condition test scores, cycle I test scores and cycle II test scores, then reflected. The results showed that through the Problem Based Learning method, it can improve the achievement of Civics learning outcomes for Grade 1 students of SD Negeri Ngemplak, Karangnongko, Klaten Semester I of the 2021/2022 academic year. The learning process of Civics material on the Formulation Process of Pancasila from cycle I to cycle II has improved: student learning outcomes from cycle I to cycle II have increased, namely from 8 students (72.7%) who got a complete score to 11 students (100%). There was an increase of 3 students (27.3%) and the class average score from 77.8 to 83.5 increased by 5.7.